Performance analysis of global and regional ionosphere maps for generation of virtual reference station - Caldeira, Mayara Cobacho Ortega; Caldeira, Carlos Rodrigo Tanajura; Alves, Daniele Barroca Marra [UNESP]; de Aguiar, Claudinei Rodrigues (My University, 2020)
An important tendency in recent years has been the use of the Real Time Kinematic (RTK) method, due to centimeter accuracy and productivity. However, the RTK is restricted to applications with a baseline below 20 km. To overcome this problem, concept of network of reference stations, called network-based positioning, has been used. However, both in use of networks and in other methods, an important factor to improve quality of positioning is related to ionospheric modeling, since this error, varies in time and space, and suffers several influences, such as: solar cycle, time of year, local time, geographic location, geomagnetic activity, among others. Currently, the errors caused by the ionosphere can have their effects minimized from IONEX files. Thus, in this research, the performance of the Global and Regional Ionosphere Maps made available, by International Service GNSS (IGS) and Monitoring the Ionosphere Over South America (MImOSA) project respectively, in positioning in networks, was analyzed, using the concept of Virtual Reference Station (VRS). According to the results obtained, observe there is accuracy in the use of the Regional Map of the MImOSA project, which has greater spatial and temporal resolution, and which presents the best results.
Análise da performance dos mapas globais e regionais da ionosfera para geração de estação de referência virtual
Keywords: Global Ionosphere Maps; IONEX; MImOSA